Swedish Sport Policy in an Era of Neoliberalism: An Expression of Social Entrepreneurship? - Bjärsholm, Daniel; Norberg, Johan R. (Frontiers in Sports and Active Living, 2021)
Since the turn of the millennium, Sweden has, like many other countries, become more neoliberal in many areas, including that of sport. The government has increased its expectations on the sports movement and become more result-oriented, which, for example, its revised motives for supporting the sports movement and the establishment of an audit organization can illustrate. However, in contrast to other countries, the Swedish government has not introduced any financial cutbacks in its support for sports. Rather, the opposite is true. The financial support has increased significantly over the last two decades. In the paper, we argue that this contradictory development of Swedish sport policy can be understood as expressions of neoliberalism and social entrepreneurship. As a theoretical concept, social entrepreneurship offers a way of understanding the increased Swedish government support for sport. There are in particular two underlying reasons for this claim. Firstly, sport is considered as a solution to various societal problems, such as social exclusion and refugee crises. Secondly, much of the increased support has been in form of various large-scale, earmarked, and time-limited political initiatives/reforms and project grants, which all have aimed to achieve social change through sport, such as social inclusion. In the paper, we consider these initiatives as expressions of social entrepreneurship. This paper contributes to the ongoing scholarly debate on how neoliberalism and neoliberal policies in the public sector have affected sport organizations. Also, by using social entrepreneurship theory, we provide new theoretical insights into how sport policy can be understood and analyzed.